Phosphorus levels and their effects on growth and intake in female alpacas in the Peruvian Andes - Quispe E., Carlos (2019)
The aim of this study was to know the levels of phosphorus and its effects on feed intake and body weight in female alpacas during the breeding season (January-February) and weaning (August-September). In the first phase, serum phosphorus levels were determined in 200 11-13-month-old alpacas, located in four alpaca regions of Peru. P levels were 8.25 ± 1.63, 5.25 ± 1.46, 6.42 ± 1.84 and 4.8 ± 1.61 mg/dl for the regions of Pasco, Junín, Cuzco and Puno, respectively, with significant differences (p<0.05) between regions. P values in one region were below the reference limit (5-11.5 mg/dl) and the another near the lower limit, which could be considered as deficient in P. In the second phase, a controlled experiment was carried out with three concentrations of P in the diet: 0.16% (T1), 0.25% (T2) and 0.34% (T3), using 16 weaned female alpacas per group (7-8 months, 25.25 ± 1.62 kg). The animals received the feeds ad libitum and were housed in individual pens for seven months. Dry matter intake was 0.717±0.82, 0.826±0.82 and 0.967±0.49 kg/animal/day and as a percentage of live weight was 2.07, 2.24 and 2.60 for treatments T1, T2 and T3, respectively. In both cases there were significant differences between treatments (p<0.05). There was a significant reduction in the concentration of P in T1 (5.02±1.11 mg/dl) compared to T2 (11.07±1.79 mg/dl) and T3 (11.45±1.14 mg/dl). It is likely that low dietary phosphorus in T1 may have affected consumption and weight gain in growing alpacas.